Patterns of opposition in the European Parliament opposing Europe from the inside? - Carlotti, Benedetta (Palgrave Macmillan, 2021)
"Practitioners and scholars have stressed the risks posed by the weakening of political legitimacy of the EU vis à vis European citizens. These conclusions are mostly drawn on speculation. This fascinating comparative study uses mixed methods to empirically explore how and when does European opposition emerge. If criticism from European citizens and political parties remains unheard within the European elitist construct, such criticism will transform itself into rejection.